Analysis Of Success Of Mandiri Mobile Banking Information System With Delone & Mclean Models - Dinda Ghassani; Sari, Agustin Rusiana (Politeknik Negeri Madiun, 2025)
The Mandiri Mobile Banking application is currently continuing to develop in order to serve its customers, this is also being done so that Bank Mandiri can compete with other banks in Indonesia. It is important for banking service providers to know the success of mobile banking in order to create strategic plans and increase the number of customers in the future. One of the models that is often used to measure the success of an information system is the DeLone & McLean Information System Success Model in which there are six constructs, namely system quality, information quality, service quality, use, user satisfaction, and net benefits. This research uses descriptive research type. The data collection technique uses the survey method by distributing questionnaires to respondents, namely Mandiri mobile banking users. The sample of this research is 385 respondents. The method of analysis in this study uses Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of the study show that all hypotheses are accepted and it is said that Mandiri mobile banking is in good condition and has been successful in providing benefits to customers who use mobile banking.